High-risk feminism in Colombia: women's mobilization in violent contexts - Zulver, Julia (Rutgers University Press, 2022)
"High-Risk Feminism in Colombia documents the experiences of grassroots women's organizations that united to demand gender justice during and in the aftermath of Colombia's armed conflict. In doing so, it illustrates a little-studied phenomenon: women whose experiences with violence catalyze them to mobilize and resist as feminists, even in the face of grave danger. Despite a well-established tradition of studying women in war, we tend to focus on their roles as mothers or carers, as peacemakers, or sometimes as revolutionaries. This book explains the gendered underpinnings of why women engage in feminist mobilization, even when this takes place in a 'domain of losses' that exposes them to high levels of risk. It follows four women's organizations who break with traditional gender norms and defy armed groups' social and territorial control, exposing them to retributive punishment. It provides rich evidence to document how women are able to surmount the barriers to mobilization when they frame their actions in terms of resistance, rather than fear"--